Efficiency of therapy for acute promyelocytic leukemia in children, by using all-trance retinoic acid, cytosine arabinoside, and smaller-dose anthracyclines - E. V. Samochatova; D. D. Baidildina; M. A. Maschan; N. N. Savva; O. P. Khlebnikova; A. V. Shamardina; Yu. E. Mareiko; G. A. Tsaur; T. O. Riger; M. M. Shneider; Yu. V. Rumyantseva; T. V. Nasedkina; et al. (Онкогематология)
The use of all-trans retinoic acid (ATRA) drastically improved the results of therapy for acute promyelocytic leukeimia (APL). The high efficiency of the Russian protocol APL-93—98 applied to 62 children and adolescents with APL (event-free and overall survival (EFS and OS) were 84±5% respectively with a relapse rate of 7%) was achieved, by administering the high cumulative dose of daunoruicin (495 mg/m2) and single doses of АТRА (45 mg/m2). In this connection, the APL-2003 protocol attempted to reduce both acute and chronic toxicity of the therapy, by decreasing the cumulative dose of daunorubicin to 405 mg/m2 and the single dose of АТRА to 25 mg/m2 under regular control of minimal residual disease via molecular monitoring of the specific transcript PML/RARα. Analysis of the results of treatment in 61 patients aged 1.3 to 17 years (median 11.3) showed that despite of the reduced protocol intensity, the efficiency of therapy did not generally reduce — EFS and OS were 79±6 and 93±3%, respectively. The likelihood of the development of a relapse was significantly affected by molecular resistance, i.e. the retention of the transcript PML/RARα before a phase of maintenance therapy: the recurrence risk in this group was 57% whereas there were no differences in all cure rates between the patients depending on baseline leukocytosis. All 6 patients with relapses were treated with arsenic trioxide, resulting in not only clinical and hematological, but also molecular remissions; thereafter the patients received myeloablative therapy and autologous hemopoietic stem cell transplantation. The second remission lasted 3 to 24 months. Thus, reducing the cumulative dose of anthracyclines and the dose of АТRА did not make the results of the therapy for APL worse. The monitoring of minimal residual disease before and during maintenance therapy is a mandatory component of successful treatment in APL patients. Arsenic trioxide is an effective agent for the treatment of APL relapses.